Utilization of brewer's spent grain in extrusion processing: A review - Kelly K. Beltrán-Borbor; Andrea D. Ortega-Suasnavas; María V. Ordóñez-Pazmiño; Diana L. Tinoco-Caicedo (Applied Food Research)
Brewers’ spent grain (BSG), the primary byproduct of the brewing industry, is rich in dietary fiber, proteins, and bioactive compounds, yet remains underutilized due to challenges such as the fiber-bound nature of bioactive compounds, antinutritional factors, and sensory limitations. This review examines extrusion technology as a transformative approach to valorize BSG, enhancing its nutritional and functional properties while addressing process scalability and environmental concerns. Key findings demonstrate that optimized extrusion parameters—temperature, moisture levels, and shear forces—facilitate the conversion of insoluble fibers into soluble forms, increase phenolic compound bioavailability, and reduce antinutritional factors such as phytic acid, improving protein digestibility. Life cycle analysis (LCA) highlights the environmental benefits of BSG extrusion, with reduced greenhouse gas emissions compared to landfill disposal, while economic studies confirm its feasibility in scalable food production. Despite these advances, sensory challenges and consumer acceptance remain critical barriers to high BSG inclusion levels in food formulations. This review underscores the need for future research on innovative pre-treatment methods, such as fermentation and enzymatic hydrolysis, and advanced extrusion techniques like reactive extrusion to further enhance BSG's functionality and application in sustainable, health-promoting food systems. These findings support the role of BSG-enriched extrudates in addressing global food security challenges, reducing environmental footprints, and contributing to the circular economy.